Structure and dynamics of benzyl-NX3 (X = Me, Et) trifluoromethanesulfonate ionic liquids - Sunda, Anurag Prakash; Dhavale, Vishal M.; Kurungot, Sreekumar; Venkatnathan, Arun (Journal of Physical Chemistry B, 2014)
Ammonium-based benzyl-NX3 (X = methyl, ethyl) trifluoromethanesulfonate (TFA) ionic liquids (ILs) are low cost, nontoxic, thermally stable ion-conducting electrolytes in fuel cells and batteries. In the present study, we have characterized the structure and dynamics of these ILs using molecular dynamics (MD) simulations and ionic conductivity using electro-chemical impedance spectroscopy (EIS) at varying temperature and relative humidity (RH). Results from MD simulations predict that cation-cation and cation-anion interactions are stronger in benzyltrimethylammonium (BzTMA) compared to benzyltriethylammonium (BzTEA) that diminish with increase in RH. Further, the BzTMA cations show both C-H/Ph (center of mass of phenyl ring) and cation-Ph interactions whereas BzTEA cations show only strong cation-Ph interactions. The C-H/Ph interactions (psi >= 90 degrees, d(H-Ph) <= 4 angstrom, theta < 50 degrees and d(C.Ph) <= 4.3 angstrom) in BzTMA cations increase with RH and are highest at RH = 90%. The cumulative impact of electrostatic, cation/Ph, and C-H/Ph interactions results in lower conductivity of BzTMA-TFA IL compared to BzTEA-TFA IL. The EIS measurements show that the trends in ionic conductivity of ILs at RH = 30 and 90% are qualitatively similar to the Nernst-Einstein conductivity from MD simulations. The ionic conductivity of BzTEA-TFA IL is similar to 3 times higher than BzTMA-TFA IL at 353 K and RH = 90%.

Surface-tuned Co3O4 nanoparticles dispersed on nitrogen-doped graphene as an efficient cathode electrocatalyst for mechanical rechargeable zinc-air battery application - Singh, Santosh K.; Dhavale, Vishal M.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2015)
The most vital component of the fuel cells and metal air batteries is the electrocatalyst, which can facilitate the oxygen reduction reaction (ORR) at a significantly reduced overpotential. The present work deals with the development of surface-tuned cobalt oxide (Co3O4) nanoparticles dispersed on nitrogen-doped graphene as a potential ORR electrocatalyst possessing some unique advantages. The thermally reduced nitrogen-doped graphene (NGr) was decorated with three different morphologies of Co3O4 nanoparticles, viz., cubic, blunt edged cubic, and spherical, by using a simple hydrothermal method. We found that the spherical Co3O4 nanoparticle supported NGr catalyst (Co3O4-SP/NGr-24h) has acquired a significant activity makeover to display the ORR activity closely matching with the state-of-the-art Pt supported carbon (PtC) catalyst in alkaline medium. Subsequently, the Co3O4-SP/NGr-24h catalyst has been utilized as the air electrode in a Zn-air battery, which was found to show comparable performance to the system derived from PtC. Co3O4-SP/NGr-24h catalyst has shown several hours of flat discharge profile at the discharge rates of 10, 20, and 50 mA/cm(2) with a specific capacity and energy density of similar to 590 mAh/g(-zn) and,840 Wh/kg(-zn), respectively, in the primary Zn-air battery system. In conjunction, Co3O4-SP/NGr-24h has outperformed as an air electrode in mechanical rechargeable Zn-air battery as well, which has shown consistent flat discharge profile with minimal voltage loss at a discharge rate of 50 mA/cm(2). The present results, thus demonstrate that the proper combination of the tuned morphology of Co3O4 with NGr will be a promising and inexpensive material for efficient and ecofriendly cathodes for Zn-air batteries.
Keywords: electrocatalyst; mixed facets; oxygen reduction reaction; rechargeable zinc-air battery; surface morphology

Strategic Preparation of Efficient and Durable NiCo Alloy Supported N-Doped Porous Graphene as an Oxygen Evolution Electrocatalyst: A Theoretical and Experimental Investigation - Singh, Santosh K.; Kumar, Deepak; Dhavale, Vishal M.; Pal, Sourav; Kurungot, Sreekumar (Advanced Materials Interfaces, 2016)
Development of an efficient and durable water splitting electrocatalyst holds a great commitment for the future energy devices. The real application of oxygen evolution reaction (OER) catalysts mainly suffers from sluggish kinetics and high overpotential except for the Ir and Ru-based systems. However, the high cost and vulnerability of the Ir and Ru metals are the main hostiles to use them for marketization. Herein, a high-performance OER electrocatalyst consisting of NiCo alloy nanoparticles supported on high surface area N-doped porous graphene (NiCo/pNGr(75: 25)) is reported. The importance of the doped-N for achieving the uniform dispersion-cum-effective interaction of the size controlled NiCo alloy nanoparticles has been explicitly investigated by transmission electron microscopy, X-ray diffraction, X-ray photo electron spectroscopy, Raman, density functional theory (DFT) calculations, etc. The electrochemical analysis of NiCo/pNGr(75: 25) shows an overpotential of approximate to 260 mV at 10 mA cm(-2) with a smaller Tafel slope of approximate to 87 mV dec(-1) and long catalytic durability. DFT calculations are done to check the interaction between the NiCo alloy nanoparticles and the defective sites of pNGr and also with the doped-N, which could be attained for maintaining long catalytic durability. Furthermore, NiCo/pNGr(75: 25) is used as an OER catalyst to fabricate an electrolyzer, which works at very low potential of 1.5 V in 1 M KOH.

Substituent‐induced deformed ni–porphyrin as an electrocatalyst for the electrochemical conversion of water into dioxygen - Krishna, J. V. S.; Krishna, Narra Vamsi; Singh, Santosh K.; Shaw, Pankaj K.; Dhavale, Vishal M.; Vardhaman, Anil Kumar; Giribabu, Lingamallu (European Journal of Inorganic Chemistry, 2018)
The electrochemical water oxidation ability of complexes 5,15‐diphenylporphinatonickel(II) (A) and 5,15‐bis(3,5‐di‐tert‐butylphenyl)porphinatonickel(II) (B) in the oxygen evolution reaction (OER) have been investigated in an alkaline medium. Complex B was found to be kinetically and thermodynamically more active than complex A. The overpotential and Tafel slope of complex B are lower than those of complex A by 30 mV and around 45 mV/decade, respectively, which supports the higher activity of B. Moreover, stability tests endorse the sustainability of both samples under alkaline conditions. It has been found that the 3,5‐di‐tert‐butylphenyl substituent in B plays a decisive role in achieving a better OER onset potential and current than that obtained with A, which is a result of the modulation of the structural parameters of B. Furthermore, the measured OER activities of A and B have been correlated with their molecular arrangement as well as differences in their bonding characteristics and dipole moments. For further insight, the obtained results have been confirmed by a theoretical study.